1999
DOI: 10.1038/sj.bjp.0702258
|View full text |Cite
|
Sign up to set email alerts
|

The effects of inflammation and inflammatory mediators on nociceptive behaviour induced by ATP analogues in the rat

Abstract: 1 We have studied the behavioural eects of intraplantar injections of adenosine 5'-triphosphate (ATP) and related compounds in freely moving rats and investigated whether these nociceptive eects are augmented in the presence of in¯ammatory mediators. 2 We ®nd that in normal animals ATP and analogues produce dose-dependent nocifensive behaviour (seen as bursts of elevation of the treated hindpaw), and localized thermal hyperalgesia. The rank order of potency was: a,b-methyleneadenosine 5'-triphosphate (a,b-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
111
0
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(127 citation statements)
references
References 32 publications
13
111
0
3
Order By: Relevance
“…PGE 2 enhanced the nocifensive reaction as well as the thermal and mechanical hyperalgesia in rats induced by ␣,␤-methylene-ATP, an activator of fast inactivating P2X receptor channels for extracellular ATP (262,759). However, ATP-(or UTP-) induced thermal hyperalgesia also depends essentially on metabotropic P2Y receptors that stimulate secondary PGE 2 formation which finally is responsible for the nociceptor sensitization, most likely achieved through sensitizing TRPV1 (462).…”
Section: Effects Of Inflammatory Mediators On Peripheral Nociceptorsmentioning
confidence: 99%
“…PGE 2 enhanced the nocifensive reaction as well as the thermal and mechanical hyperalgesia in rats induced by ␣,␤-methylene-ATP, an activator of fast inactivating P2X receptor channels for extracellular ATP (262,759). However, ATP-(or UTP-) induced thermal hyperalgesia also depends essentially on metabotropic P2Y receptors that stimulate secondary PGE 2 formation which finally is responsible for the nociceptor sensitization, most likely achieved through sensitizing TRPV1 (462).…”
Section: Effects Of Inflammatory Mediators On Peripheral Nociceptorsmentioning
confidence: 99%
“…The injection of ATP analogues into the hindpaw of rats has also been reported to elicit nociceptive paw-lifting behavior (Hamilton et al, 1999), while intrathecal administration of ATP analogues produces thermal hyperalgesia (Tsuda et al, 1999). These responses indicate that ATP can evoke pain which is now known to be mediated via ATP purinoceptors (for review, see Hwang and Oh, 2007;Wirkner et al, 2007).…”
Section: Atp P2x 3 Receptors and Painmentioning
confidence: 99%
“…Paukert et al 32) showed that inflammatory mediator such as substance P and bradykinin potentiate the ATP-evoked currents in oocytes expressing P2X3 by lowering the desensitization rate through phosphorylation of P2X3. Hamilton et al 7) also reported that nociceptive action of ATP are markedly augmented in the presence of inflammation or inflammatory mediators and it was attributed that extracellular levels of ATP will reach levels capable of activating nociceptors in inflamed tissue. There are several ways in which the enhanced responses might arise.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…ATP can be released actively or passively by cell lysis during tissue damage, which in turn may activate P2X3 receptors to initiate nociceptive signals. This effect may be exaggerated under conditions of inflammation 6,7) . Many previous studies showed the expression of P2X3 in the central and peripheral neurons 1,4,[8][9][10] .…”
Section: ⅰ Introductionmentioning
confidence: 99%